Phytochemical compounds (Andographolide, Gallic Aicd, Curcumin And Artemisinin) as a potential inhibitor for sars cov 2: a review / Ahmar Yusry Yusof - Yusof, Ahmar Yusry; Jamil, Muhammad Hakimi; Ramli, Nur Aleeya Natasha; Roslan, Nursyaheera Amila
COVID-19, a new pandemic caused by SARS-CoV-2, was first identified in 2019 in Wuhan, China. The novel corona virus SARS-CoV-2 and the 2002 SARS-CoV have 74 % identity and use similar mechanisms to enter the cell. Phytochemicals are defined as bioactive nutrient plant chemicals in fruits, vegetables, grains, and other plant foods that may provide desirable health benefits beyond basic nutrition to reduce the risk of major chronic diseases. In this case, the phytochemicals that are in focus are Andrographolide which is from the Andrographis plant, Curcumin that can be found in turmeric plant, Gallic Acid from parts of various plants and Artemisinin which can be found in the sweet wormwood plant, Artemisia annua. These phytochemicals are chosen because these compounds can obtain abundantly in Malaysia Herbs and based on their effectiveness as antioxidant reducing respiratory system problem. The study focuses on research done on published literal researches of the phytochemicals being virtually tested on the SARS-CoV2 viruses through in silico study. These phytochemicals have been virtually confirmed to be a viable compound in fighting against SARS-CoV2 through various bindings on the viruses' protease component. However, further research is necessary to investigate the ability of these compounds as viral entry inhibitors.